The Concept of Patriotism in The Mind of Youth - Polatov Baxodir; Abdullayev Baxriddin; Toxtanazarov Ilhomjon; Yusupov Arabboy (Zien Journals, 2022)
the concept of patriotism in the mind of youthThis article reiterates the importance of patriotism.
Keywords: idea of independence; national; CHQBT; need, in vain